The Effect of Various Active Ingredients of Fungicides Against Anthracnose Disease (Colletotrichum gloeosporioides) in Chili Plants (Capsicum annuum L.) - Fauzi, Rizal Ahmad; Syaefullah, Mohamad Alwi; Dwitama, Muhammad Fachri; Deden, Deden; Dukat, Dukat (Devotion : Journal of Research and Community Service, 2023)
The numerous benefits and uses of chilies have led to a constant increase in demand as the population of Indonesia grows. Anthracnose is a disease that often affects chili peppers and is caused by the fungus Colletotrichum gloeosporioides. Farmers typically use fungicides to control anthracnose. Common active ingredients applied for anthracnose control include Mancozeb, Chlorothalonil, Propineb, and copper hydroxide. The research was conducted in the village of Ambit, Waled District, Cirebon Regency, West Java Province. The study took place over three months, from July to September 2023. The research method used a Randomized Group Design (RGD) consisting of five treatments with different active fungicide ingredients and a control (without treatment), repeated five times, resulting in 25 experimental plots. The treatments were A (Copper hydroxide active ingredient), B (Mancozeb active ingredient), C (Chlorothalonil active ingredient), D (Propineb active ingredient), E (Control /no fungicide). The fungicide concentration used was 2 ml/liter. The experimental results showed that the various active fungicide treatments had a significant effect on the intensity of anthracnose disease (Colletotrichum gloeosporioides) and other diseases like gemini virus. The Chlorothalonil active ingredient showed the lowest intensity of disease anthracnose when compared to the other treatments, even with other active ingredients that were tested. Fungicide treatments had a significant impact on chili yields per plot compared to the control treatment without fungicide. The Chlorothalonil active ingredient treatment yielded higher chili harvest results compared to other treatments, reaching 15.97 kg/plot or 15.97 tons/ha.